Middle School Reading Comprehension and Content Learning Intervention for Below-Average Readers. Issue 1 (2nd January 2017) - Swanson, Elizabeth; Wanzek, Jeanne; Vaughn, Sharon; Fall, Anna-Maria; Roberts, Greg; Hall, Colby; Miller, Veronica L.
ABSTRACT: This study aimed to determine the efficacy of a content knowledge and reading comprehension treatment implemented by 8th-grade social studies teachers over the course of 1 school year. We randomly assigned 8th-grade students with reading difficulties to the intervention treatment condition ( n = 45) or the business-as-usual comparison condition ( n = 33). Students in the treatment condition scored statistically higher than students in the comparison condition on measures of knowledge acquisition (effect size [ES] = 0.35), content reading comprehension (ES = 0.59), and vocabulary recall (ES = 0.65). The small ES on standardized reading comprehension (ES = 0.10) favoring the treatment condition was not statistically significant.